Dynamic Governance in the Development of Santri City in Bireuen District - Nofica, Idza; Yani, Ahmad; Alfiady, Teuku Alfiady; Syamsuddin, Syamsuddin; Muryali, Muryali (International Journal of Public Administration Studies, 2024)
This study examines the concept of Dynamic Governance in Bireuen District regarding the designation of Bireuen as "Santri City." The title of Bireuen as Santri City is based on Circular No. 451/975/2020 and Regents Decree No. 553/2020, which officially declared Bireuen as a Santri City. Bireuen District earned this designation due to the presence of numerous Islamic boarding schools (dayahs) and pesantren, as well as rapidly growing religious study centers (balai pengajian). This research aims to explore the extent to which government departments innovate in developing Bireuen as a Santri City. The objectives of this research are to understand the concept of dynamic governance in the context of Santri City in Bireuen and to evaluate the programs that have been implemented concerning this designation.This research employs a descriptive qualitative approach. The researcher utilized two types of data sources: primary and secondary data. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data collection, data presentation, and drawing conclusions. The findings indicate that dynamic governance in Bireuen District has not been effectively implemented, with limited community participation in the innovative ideas introduced by the government. The study evaluates this through three indicators: Thinking Ahead, where the Bireuen Regency Government issued innovations such as a circular banning live music and a warning against Valentines Day celebrations; Thinking Across, with actions by the Public Order and Peace Agency (Satpol PP and WH) that involved community outreach, such as socializing with youth and village communities, promoting Islamic attire, and monitoring tourist spots; and Thinking Again, where the agency focused on educating school youth and village officials from 2021 onwards, coupled with monitoring at tourist locations. The designation of Bireuen as Santri City not only benefits the community in terms of education but also economically, as local residents can engage in business activities around dayahs, thus boosting their income.